Endoscopic removal of frontoethmoid osteoma: A case report - (:unkn) unknown (My University, 2005)
Osteoma is the most common benign tumor of the nose and paranasal sinuses. Most commonly seen in the frontal sinus, it is less common in the ethmoid and maxillary sinuses. This tumor may be discovered incidentally on radiographs, or may grow enough to produce symptoms. Rarely, complications occur at its location near the orbit and anterior skull base. We present a case of frontoethmoid osteoma treated by endoscopic resection, and we emphasise the advantages of this minimally invasive method compared with traditional methods.
Keywords: Endoscopic approach; Frontoethmoid region; Osteoma